International art exhibit sales reach $11,000 (Raton, NM Raton Range, 1996)
Article is about the Annual International Art Exhibit and sale held by the Old Pass Gallery.
Newspaper article
Master list item #: 105
File location is in the Raton file Cabinet
Keywords: Hughes, Sam -- Artist; Andera, Mary Ann -- Artist; Peterson, Lois -- Artist; Franco, Manuel -- Artist; Lind, Richard -- Artist; Newton, Marv -- Artist; Sowers, Jimmie Nell -- Artist; Siefert, Ginnie -- Artist; Pavletich, L. Martin -- Artist; Techenor, Narice -- Artist; Parks, Frances -- Artist; Chavez, Henry -- Artist; Sanchez, Kathy -- Artist; Conine, Colleen -- Artist; Alsup, Sue -- Artist; Petersen, Alan -- Artist; Ashcraft, Mitzi -- Artist; Reeser, Jean -- Artist; Art Show; Art Exhibit; Art and Humanities Council Promotion; Art Sales; Art Promotion; Raton, New Mexico